The impact of the approach taken to the effectiveness of teaching ran barriers to learning according to the method of knowledge [Stability - polishing] - Hatim, nagham (Journal of Physical Education, 2012)
Methods is the knowledge of important concepts in psychology and that they relate to the feelings of individuals and their behavior in different situations, and that the method of cognitive consistency versus refinement is one of the leading methods that reflect the speed and accuracy of the respondents to answer in the learning. The importance of these cognitive styles was the importance of this research to predict with a reasonable degree of handling an individual with information in terms of his style of thinking and his way of understanding and remembering in the course of their response to various life situations. The aim of the research to: 1. Study the effect of the approach taken to the effectiveness of teaching ran barriers to learning in the knowledge my learning in the knowledge my sample method (stability and polishing). To investigate the objectives of the research assumed the following: 1. There are significant differences between tribal and post tests and for the post-test to learn the effectiveness of the barriers ran a sample search. This section contains the theoretical studies addressed by the researcher on the subject of research is customary methods, types, characteristics and theories of knowledge, including the method (stability versus refinement), and the method of processing information and sovereignty cortex (right, left, Integrated). Contains this section on the use of descriptive method with experimental design using a single set of tests tribal and post on a sample composed of (62) students from the second stage in the Faculty of Physical Education at the University of Baghdad and the academic year 2010-2011 m, and ran on the effectiveness of barriers. Where the application of the method of knowledge (stability - polishing) to sample the whole, and the method of information processing, and finally "the sovereign brain, which divided the sample into three classes left and right and integrated. The researcher used a test assessing the technical performance of ran barriers, has been the implementation of researchprocedures according to the curriculum teaching prepared by the college and under the supervision of Dr. Shakir Mahmoud Sheikhly at the rate (16 and module), preceded by two units at a rate of Tarevican (2 modules) in the week. (12 and module), preceded by two units at a rate of Tarevican (2 modules) in the week. After a tribal and post tests were treated by statistical means appropriate This section contains the results of the methods used in the study with the analysis and discussion of test by assessing the technical performance of the students ran the barriers, to achieve the research objectives and hypotheses. This section contains a set of conclusions, including: 1. Cognitive consistency that the method may return polishing products to the research sample (3.82%) and refinement of a group (7.77%) of group stability. Through the conclusions reached by the researcher to recommend the following: 1. Use the method of knowledge refinement in stability compared to other research different and that by linking a number of variables such as learning styles, motivation, etc. 2. Use other methods of knowledge in the educational process through which can be distinguished among the students.